FAKTOR-FAKTOR YANG MEMPENGARUHI KEBIJAKAN HUTANG DAN NILAI PERUSAHAAN: STUDI EMPIRIK PADA PERUSAHAAN SEKTOR NONJASA DI BURSA EFEK INDONESIA PERIODE 2007-2010 - Nurhayati, Mafizatun (Faculty of Economics Universitas Atma Jaya Yogyakarta, 2012)
This study was conducted to examine the infl uence of factors of company size, business risk, liquidity(current ratio), and profi tability (return on assets / ROA) to the policy of debt (debt to asset / DTA) andenterprise value (price book value / PBV ) through empirical studies on non-service fi rms that go public onthe Stock Exchange Indonesia Year 2007-2010.The population in this study were 425 companies listed onthe Indonesia Stock Exchange in the period 2007-2010. Sampling technique used was purposive sampling,with the following criteria: (1) a company that is always present its fi nancial statements for 2007-2010, and(2) a company that is continuously distributed dividends every period 2007-2010. Data obtained from thepublication in the website Stock Exchange, namely www.idx.co.id. Thence obtained the sample of 108companies. Analytical technique used is the path analysis.The results showed that the size of the companyhave a positive and signifi cant impact on debt policy. Business risk has a negative but not signifi cant infl uenceon debt policy. Company’s liquidity (Current Ratio) has a negative and signifi cant impact on debt policy.Corporate profi tability has a negative and signifi cant impact on debt policy. Firm size has a signifi cant positiveeffect on fi rm value. Business risk has no signifi cant negative effect on fi rm value. Company’s liquidity (Currentratio) does not have a signifi cant infl uence on the value of the company. Corporate profi tability has a positiveand signifi cant impact on fi rm value. Debt policy does not signifi cantly infl uence the value of the company.Keywords: Current ratio, fi rm size, return on assets, Debt to Asset, Price Book Value.